2008
DOI: 10.1186/1471-2229-8-1
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinformatic analysis of the CLE signaling peptide family

Abstract: Background: Plants encode a large number of leucine-rich repeat receptor-like kinases. Legumes encode several LRR-RLK linked to the process of root nodule formation, the ligands of which are unknown. To identify ligands for these receptors, we used a combination of profile hidden Markov models and position-specific iterative BLAST, allowing us to detect new members of the CLV3/ESR (CLE) protein family from publicly available sequence databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
283
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(310 citation statements)
references
References 64 publications
14
283
4
Order By: Relevance
“…17 MtCLE12/MtCLE13) were constitutively expressed in hairy roots after transformation with Agrobacterium rhizogenes. In both legumes, overexpression of these CLE peptides under the control of the CaMV 35S promoter suppressed nodule formation in nontransgenic parts of the root system.…”
Section: Shoot-controlled Autoregulation Of Nodulationmentioning
confidence: 99%
“…17 MtCLE12/MtCLE13) were constitutively expressed in hairy roots after transformation with Agrobacterium rhizogenes. In both legumes, overexpression of these CLE peptides under the control of the CaMV 35S promoter suppressed nodule formation in nontransgenic parts of the root system.…”
Section: Shoot-controlled Autoregulation Of Nodulationmentioning
confidence: 99%
“…In recent years, individual experiments have demonstrated that small proteins (<200 amino acids [aa] in length), encoded by short open reading frames (sORF), play a major role in plant and animal development, e.g., the TAL protein (11 aa) influencing fruit fly development (Galindo et al 2007), the Cg-1 protein (<33 aa) controlling the tomato-nematode interaction (Gleason et al 2008), the CLE family proteins (75-140 aa) (Fletcher et al 1999;Trotochaud et al 2000;Muller et al 2008;Oelkers et al 2008) involved in Arabidopsis meristem development, the galectin-1 protein (;130 aa) associated with the malignant human tumor progression (Camby et al 2006), the lipid-binding protein AZI1 (161 aa) involved in priming plant defenses (Jung et al 2009), and the FLOWERING LOCUS T (FT) protein (175 aa) acting as a long-range signal regulating flowering (Notaguchi et al 2008). …”
mentioning
confidence: 99%
“…The CLV3 gene is expressed exclusively in stem cells of the aboveground meristems [9,10], and acts as a secreted signalling peptide. All predicted CLE peptides share a conserved C-terminal motif, which forms the core of the active peptide [11,12]. Overexpression of CLE genes in transgenic plants grown in liquid cultures and purification of extracellular peptides from the medium allowed determination of the structure of the active peptide [13,14].…”
Section: The Clavata Pathway As a Paradigm For Intercellular Communicmentioning
confidence: 99%